Keberhasilan Bantuan Luar Negeri di Asia Timur Laut: Sebuah Pembelajaran Bagi Negara Berkembang - Ardila Putri; Silvia Dian Anggraeni; Radika Ayu A (Andalas Journal of International Studies (AJIS), 2020)
After the second world war, Northeast Asian countries such as Japan, South Korea, China and Taiwan, were recipient countries of foreign aid. Then, the countries changed its status from the recipient countries to the donor countries. This paper aims to explain the factors that led to the success of Northeast Asian countries to change their status from foreign aid recipient to foreign aid providers. This research departs from the tradition of empiricism and is a qualitative research using descriptive-analytical methods. This research shows that good governance, the close relations between donor countries and recipient countries, as well as huge investments in infrastructure and human resources are the key to the success of foreign aid in Northeast Asian countries. This study concludes that the country's enormous role (ownership) in the management of foreign aid is the most influencing factor.